REVIEW OF THE DEFINITIONS OF PROPOSITIONS AND STATEMENT IN THEIR RELATIONSHIP WITH MATHEMATICS - Hurtado Mondoñedo, Luis Leoncio (2017)
In mathematics we work with propositions. The term proposition is taken from logic and is usually defined as a statement that can be qualified as true or false. A proposition is considered as a formulation, and this is a phrase or sentence. According to the above, for example, the expression 3 < 7, which is clearly a true statement from the field of mathematics, would not be such according to what was expressed above. This article reviews the definitions of logic, proposition and statement taken in a sample of high school and college texts that deal with the subject and, on that basis, the consistency of the definitions of proposition and statement are analyzed, as well as their relevance in relation to mathematics.